Box Traffic/Underpass Structure Calculation Analysis (Case Study of Box Traffic/Underpass on Kuala Tanjung – Indrapura Toll Road Section II Zone 2) - Sihombing, Alexander Tuahta; Hura, Irwan (Budapest International Research and Critics University, 2021)
The purpose of this study was to determine the feasibility of planning box traffic/underpass on the Kuala Tanjung-Indrapura toll road. So that later the results of the planning can be used as a reference for planning similar structures. The author's objectives from the implementation of this final project are: 1) Knowing the magnitude of the load value that occurs in the box traffic/underpass building structure. 2) Knowing the feasibility of the strength of the planned traffic/underpass structure. 3) Analyze the structure of the box traffic/underpass that has been planned. After analyzing and designing using the SAP 2000 Program on the BOX TRAFFIC/UNDERPAS Building on the Kuala Tanjung – Indrapura Toll Road Section II Zone 2 which is adjusted to the Procedure for Calculation of the Bridge Loading Regulations according to SNI 1725-2016 and RSNI T-02-2005, based on structural analysis which is reviewed, it can be concluded that in the planning of box traffic/underpass, it is in accordance with the standard of bridge loading planning.